Introduction to Physiological Psychology - Levinthal, Charles F (Prentice-Hall of India, 1990)
This lucidly written beginner's text on the physiology of human behaviour reflects not only traditional areas of the field, but the cutting edge of new research as well. Highly practical in focus, it explores the ways in which physiological psychology fits into the larger framework of psychology in general, and examines the ways in which it can be applied to everyday human experiences. Throughout, the author presents models of behaviour and experiences that center around the neurotransmitter or hormonal processes in the nervous system and focuses on theory and data regarding the physiological bases of human behaviour. Special chapters cover brain chemistry and its hemispheric specialisation and lateralisation. The third edition features : discussion of major breakthroughs in physiological psychology since 1982, a focus on Parkinson's disease and Alzheimer's disease, New section on circadian rhythms, new information on brain scanning techniques, "neuroscience focus" boxes at the end of each chapter and updated information on the role of endomorphins in analgesia, social bonding and emotionality.